2005
DOI: 10.1007/s00464-004-8184-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy versus open left lateral segmentectomy for recurrent pyogenic cholangitis

Abstract: This study not only confirmed the feasibility of hand-assisted laparoscopic segmentectomy for recurrent pyogenic cholangitis, but also showed that this treatment approach is associated with less pain and shorter hospital stay. However, hand-assisted laparoscopic segmentectomy is a lengthier operation and technically more challenging. Nevertheless, the authors believe that with more experience and further improvement of ancillary technology, this procedure can become a standard treatment for recurrent pyogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 10 publications
2
31
0
3
Order By: Relevance
“…1 and 2, six studies [4][5][6][7][8][9] compared the operative time between the two groups and found that the operative time was 48.07 min (95% CI, 30.93-65.21) shorter in the open group than in the laparoscopic group. This difference was significant (p \ 0.001) and not associated with significant heterogeneity between the studies (p = 0.34).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…1 and 2, six studies [4][5][6][7][8][9] compared the operative time between the two groups and found that the operative time was 48.07 min (95% CI, 30.93-65.21) shorter in the open group than in the laparoscopic group. This difference was significant (p \ 0.001) and not associated with significant heterogeneity between the studies (p = 0.34).…”
Section: Resultsmentioning
confidence: 98%
“…5 and 6, four studies [5,6,9,10] documented the duration of hospital stay in each group. The hospital stay in the laparoscopic group was 4.52 days (95% CI, -8.03 to -1.02) shorter than in the open group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Definitive treatment usually involves resection of the stone-harbouring segments. Recent studies have shown that hand-assisted laparoscopic segmentectomy is not only feasible in this condition, but is also associated with less post-operative pain and a shorter in-patient hospital stay [12].…”
Section: Discussionmentioning
confidence: 99%